A Numerical Model to Predict the Anisotropy of Polymer Composites Reinforced with High-Aspect-Ratio Short Aramid Fibers - Jianhong Gao; Xiaoxiang Yang; Lihong Huang (Advances in Polymer Technology)
Some fiber types have a high aspect ratio and it is very difficult to predict their composites using traditional finite element (FE) modeling. In this study, an FE model was developed to predict the anisotropy of composites reinforced by short aramid fibers. Three fiber distribution types were studied as follows: perfectly aligned, normally distributed, and randomly distributed fibers. The elastic constants were obtained, and, for different alignment angles and parameters in the fiber orientation distribution function, their numerical results were compared to those of the Mori–Tanaka model. Good agreement was obtained; thus, the employed FE model is an excellent and simple method to predict the isotropy and anisotropy of a composite with high-aspect-ratio fibers. Therefore, the FE model was employed to predict the orientation distribution of a composite fiber with a nonlinear matrix. The predicted and experimental results agree well.